Bonding failure mechanism of corroded concrete beams under different anchored types: Experimental study - Yuanyuan Li; Lei Huang; Ruxin Wang; Liangtai Yan; Panfeng Ba; Caiwei Liu (Case Studies in Construction Materials)
The current research on bonding performance is mainly obtained through cubic pull-out specimens, while the bonding performance of the end anchorage specimens of rebars under bending loads is not clear. Therefore, 30 beam specimens were designed for bending tests to explore the enhancement effect of rebar anchorage and the corrosion deterioration effect on bonding properties. The anchored beams with varying corrosion degrees were designed through an accelerated corrosion test, and a subsequent flexural bending test was performed. The flexural test results indicate that the slip resistance of the anchored beam is larger than that of the unanchored beam, and the bonded coefficient of the anchored beam is 175.8 % of that of the unanchored beam. The end anchorage of rebar increases the bond performance and deformation capacity and improves the ultimate bearing capacity of the corroded structures. When the theoretical corrosion degree is 10 %, the energy dissipation capacity of non-anchored beams is 69.65 % of that of anchored beam specimens. Based on the SEM and EDS analysis of the bonded fracture specimen, the damage area of the bonded fracture surface of the anchored beam specimen is 10.58 % larger than that of the non-anchored beam specimen when the actual corrosion degree is 9.25 %. The energy dissipation capacity of the anchored beam increases with the increase of embedded length, and the bending moment calculation formula was proposed considering the corrosion degree and anchorage coefficient. A formula for calculating crack width based on corrosion damage and anchorage enhancement effect was also presented, and the failure strain and slip of the bonding section were quantified. Finally, the bond stress-strain constitutive models of beams with different anchoring types were obtained, and the accuracy of the calculated models was verified by the finite element model and failure probability model. This study investigated the bonding fracture mechanics of anchored structures under a corrosion environment, and the failure constitutive model of anchored beams is of great significance to the failure safety evaluation of service structures.